ANTI-BIOFOULING ACTIVITY OF SPONGE Callyspongia pseudoreticulata COMPONENTS EXTRACT AGAINST Balanus amphitrite - Rosmiati, Rosmiati; Harlina, Harlina; Parenrengi, Andi; Suryati, Emma; Irmawati, Irmawati (Agency for Marine and Fisheries Extension and Human Resources, 2024)
Biofouling attached to floating net cages and other aquaculture containers is an obstacle in aquaculture. The presence of biofouling can reduce the quality of the environment and interfere with the health of farmed animals, resulting in large losses. This study assessed the anti-biofouling activity of the Callyspongia pseudoreticulata extract component (EMCp) against the Barnacle Balanus amphitrite. For this purpose, C. pseudoreticulata was extracted with 80% methanol using the maceration method at <40°C to obtain EMCp. B. amphitrite was cultured in an aquarium at 25 ppt. The anti-biofouling activity of EMCp was tested against B. amphitrite larvae using asbestos plates. The study used a Complete Randomized Design with three treatments, namely, A) asbestos plate smeared with EMCp + varnish, B) asbestos plate smeared with varnish, and C) asbestos plate not smeared with EMCp and varnish (control). EMCp toxicity test on the larvae used clear bottles, and the adhesion test using 24-well polystyrene plates. Toxicity observations were done after 24 hours, and the number of dead larvae was calculated. The attachment of the larvae was calculated under a microscope at 10× magnification. Identification of groups of chemical compounds using a thin-layer chromatography chromatogram detected under UV lamps and spraying of reagents. The study found that EMCp effectively inhibited the attachment and growth of B. amphitrites with the LC50 of 150 mg/L. Studies of chemical constituents identified various compounds in the extract, including alkaloids, flavonoids, and terpenoids. These results suggest that C. pseudoreticulata has potential as a natural alternative to chemical-based antifouling agents.